The Effectiveness of Problem-Based Learning E-Modules on Students' Problem-Solving Skills and Cognitive Learning Outcomes: A Systematic Review - Salwa Salwa; Neli Juliani; Irman Muliadi; Sumarti Sumarti (Indonesian Journal of Innovation and Educational Technology, 2026)
This systematic literature review (SLR) evaluates the effectiveness of Problem-Based Learning (PBL)-integrated e-modules in enhancing students' problem-solving skills and cognitive learning outcomes. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a comprehensive search was conducted across Google Scholar, Garuda (SINTA), ERIC, and Scopus databases for articles published between 2016 and 2025. From an initial pool of 76 identified studies, 25 met the predefined inclusion and exclusion criteria for analysis. The findings demonstrate that PBL-based e-modules significantly improve problem-solving skills, evidenced by an average N-gain ranging from 0.60 to 0.78 (medium to high category). Similarly, cognitive learning outcomes showed a marked increase, with average score improvements of 15% to 35% from pre-test to post-test. Key factors contributing to this effectiveness include the structured problem-based approach, interactive e-module features, and the integration of contextual real-world issues. This review concludes that PBL-based e-modules are a potent instructional tool for fostering critical skills and academic achievement across various educational levels.